Evaluation of the Results of Closed Antegrade Interlocking Intramedulary Nail for Proximal and Mid Shaft Femur Fracture - Hasan, Md Habibul; Alam, Md Shah; Azad, Md Abul Kalam; Md Ahsanuzzaman, - (TAJ: Journal of Teachers Association, 2020)
Background: Fractures of the shaft of the femur are among the most common fractures encountered in orthopedic practice. Various treatment options are available but closed interlocking intramedullary nail for fracture shaft of the femur is the gold standard treatment. Objectives: This randomized clinical trial was conducted to evaluate the results of closed intramedullary interlocking nailing for proximal and mid shaft femoral fractures in adult in our country. Materials and Method: This study was conducted at the National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Sher-E-Bangla Nagar, Dhaka and private Hospital of Dhaka and Rajshahi over a period of four and half years (August 2013-August 2017). Adult patients with closed fracture of proximal and mid shaft of the femur were the study population. A total of 50 patients (50 femoral shaft fractures) aged 18-65 years irrespective of sex were included in the study. The mean age of the patients was 36.52 ± 15.24. Majority of the patients were male. Twenty seven (54%) patients were operated on left side and twenty three (46%) patients were operated on right side. Average time interval between injury and date of surgery was 8.26 days and average time of operation was 95 minutes. Results: 42 patients (84%) has found union within 20 weeks, 6 patients (12%) has found delayed union and was dynamized and united, 01(2%) patient has lost follow up and 01(2%) patient has died at home at 16th post-operative day. Full range of knee movements was found in all cases. Conclusion: Closed locking intramedullary nailing for fracture proximal and mid shaft of the femur is a good option due to less infection, early healing and less scar formation, good range of knee and hip movement. TAJ 2019; 32(2): 27-35